2009
DOI: 10.1002/biof.41
|View full text |Cite
|
Sign up to set email alerts
|

Roles and regulation of Thy‐1, a context‐dependent modulator of cell phenotype

Abstract: Thy-1, or CD90, is a glycophosphatidylinositol-linked glycoprotein expressed on the surface of neurons, thymocytes, subsets of fibroblasts, endothelial cells, mesangial cells and some hematopoietic cells. Thy-1 is evolutionarily conserved, developmentally regulated, and often has dramatic effects on cell phenotype; however the effects vary between and in some cases within cell types and tissues, and between similar tissues in different species, indicating that the biological role of Thy-1 is context-dependent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 67 publications
1
95
0
5
Order By: Relevance
“…The biological role of Thy-1, like that of CD97, is context dependent (30). Thy-1 distribution in mice differs from that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The biological role of Thy-1, like that of CD97, is context dependent (30). Thy-1 distribution in mice differs from that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Kinetic analysis has shown that Thy-1 mRNA and proteins are gradually lost over the first 2 weeks following optic nerve crush. 17 RGC death follows around 1 to 2 weeks after Thy-1 loss.…”
mentioning
confidence: 99%
“…Na literatura o CD90 é também conhecido como Thy-1 e citado como marcador de timócitos e mioblastos pouco diferenciados, células neurais, células endoteliais, além de ser um marcador pan-linfócitos T (Sumikuma et al, 2002;Bradley et al, 2009;Wisniewski et al, 2011;Alt et al, 2011, Lin et al, 2013. Este marcador também é encontrado em células epiteliais progenitoras (Nakamura et al, 2006), fibroblastos (Alt et al, 2012) e CTMs (Dominici et al, 2006;Alt et al, 2011;Karamzadeh et al, 2012;Orbay et al, 2012).…”
Section: Cd90unclassified
“…Cell Initiative, 2007), células-tronco hematopoiéticas (Bradley et al, 2009;Karaöz et al, 2010;Orbay et al, 2012), assim como em células-tronco mesenquimais dereivadas de tecidos dentais (Horwitz et al, 2005;Dominici et al, 2006;Lorenz et al, 2008;Xu et al, 2009;Pivoriuunas et al, 2010;Iohara et al, 2011;Mitterberger et al, 2012;Orbay et al, 2012;Mafi et al, 2011;Lin et al, 2011;El-Syed et al, 2012;Hidaka et al, 2012;Bakopoulou et al, 2013).…”
Section: O Cd90 Também é Encontrado Em Células-tronco Embrionárias (Iunclassified
See 1 more Smart Citation